UPAYA MENINGKATKAN MOTIVASI DAN PRESTASI BELAJAR MENGGUNAKAN MODEL NUMBERED HEADS TOGETHER (NHT) PADA SISWA KELAS XI TKR 4 SMK GANESHA TAMA BOYOLALI - Satrio Khabib; Suharno Suharno; Ngatou Rohman (Nozel : Jurnal Pendididikan Teknik Mesin, 2019)
The objectives of this research are to improve: (1) the learning motivation in the Vocational Competency subject matter through the Numbered Heads Together (NHT) learning model; and (2) the learning achievement in the Vocational Competency subject matter through the Numbered Heads Together (NHT) learning model.This research used the classroom action research with two cycles. Each cycle consisted of three meeting. Each meeting lasted for 2 x 45 minutes. Its subjects were the students as many as 33 in Grade XI-Light Vehicle Engineering Program 4 of Ganesha Tama Vocational High School of Boyolali. The research was collaborative in nature among the researcher, subject matter teacher, observer, and students. It began with simulation on the subject matter teacher. The data of research were collected through observation, test, questionnaire, and documentation. The procedure of research included the following stages: (1) action planning, (2) action implementations, (3) observation and interpretation, and (4) analysis and reflection.  The result of research shows that there is an improvement of learning motivation and achievement in the Vocational Competency subject matter in terms of process and product through the application of the NHT learning model. In cycle I the learning motivation was 73.61%, and it became 77.30% in cycle II. Moreover, the number of the students who gained improvement in the learning achievement was 22 (66.67%) in cycle I, and 27 (82.00%) in cycle II.